Cells on hierarchically-structured platforms hosting functionalized nanoparticles. (6th April 2018) - Simitzi, Chara; Harimech, Pascal; Spanou, Syrago; Lanara, Christina; Heuer-Jungemann, Amelie; Manousaki, Aleka; Fotakis, Costas; Ranella, Anthi; Kanaras, Antonios G.; Stratakis, Emmanuel
Abstract : In this work, we report on a novel approach to develop hierarchically-structured cell culture platforms incorporating functionalized gold nanoparticles (AuNPs). Abstract : In this work, we report on a novel approach to develop hierarchically-structured cell culture platforms incorporating functionalized gold nanoparticles (AuNPs). In particular, the hierarchical substrates comprise primary pseudo-periodic arrays of silicon microcones combined with a secondary nanoscale pattern of homogeneously deposited AuNPs terminated with bio-functional moieties. AuNPs with various functionalities ( i.e. oligopeptides, small molecules and oligomers) were successfully attached onto the microstructures. Experiments with PC12 cells on hierarchical substrates incorporating AuNPs carrying the RGD peptide showed an impressive growth and NGF-induced differentiation of the PC12 cells, compared to that on the NP-free, bare, micropatterned substrates. The exploitation of the developed methodology for the binding of AuNPs as carriers of specific bio-functional moieties onto micropatterned culture substrates for cell biology studies is envisaged.